2020
DOI: 10.21203/rs.3.rs-22141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The timeline and risk factors of clinical progression of COVID-19 in Shenzhen, China

Abstract: Abstract Background The novel coronavirus disease 2019(COVID-19) broke out globally. Early prediction of the clinical progression was essential but still unclear. We aimed to evaluate the timeline of COVID-19 development and analyze risk factors of disease progression.Methods In this retrospective study, we included 333 patients with laboratory-confirmed COVID-19 infection hospitalized in the Third People's Hospital of Shenzhen from 10 January to 10 February 2020. Epide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…Closer examination of non-invasive respiratory support use patterns revealed that the highest probabilities of requiring HFNC or NIPPV occurred relatively early in the hospital course, consistent with other studies reporting deteriorating respiratory status and development of ARDS soon after admission (4, 5, 32). Notably, we found that the median time to treatment failure was within two days after initiation of HFNC or NIPPV, highlighting that the immediate period after initiation of non-invasive respiratory support represents a crucial window for clinical deterioration and progression of disease.…”
Section: Discussionsupporting
confidence: 86%
“…Closer examination of non-invasive respiratory support use patterns revealed that the highest probabilities of requiring HFNC or NIPPV occurred relatively early in the hospital course, consistent with other studies reporting deteriorating respiratory status and development of ARDS soon after admission (4, 5, 32). Notably, we found that the median time to treatment failure was within two days after initiation of HFNC or NIPPV, highlighting that the immediate period after initiation of non-invasive respiratory support represents a crucial window for clinical deterioration and progression of disease.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, patients hospitalized with underlying conditions presented worse lymphocytopenia than those who did not report comorbidities [ 178 , 185 , 186 , 187 , 189 ]. Based on this information, the majority of the researchers have proposed that lymphocytopenia could potentially be used as an indicator of COVID-19 severity [ 190 , 191 , 192 ]. Conversely, to what is reported about the quantitative aspects of T-cell populations during the COVID-19 course, an aspect in which there is a pronounced lack of understanding is whether T-cell response might positively or negatively contribute towards the severity of this disease [ 193 ].…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%
“…It has been reported that compared with non-ICU patients, ICU patients have a higher proportion of diabetes. Additionally, it is also suggested that DM may affect the clinical manifestations and patient's disease progression (7).…”
Section: Introductionmentioning
confidence: 99%